Find all values of c such that 3*(2c + 1) = 28*(3*c) - 9. If you find more than one value of c, then list your values in increasing order, separated by commas.

Guest Jan 27, 2023

#1**+1 **

we start with 3(2c+1) = 28(3*c) - 9

(just to note 3*c = 3c)

we expand the equation by multiplying the numbers left unmultiplied

3(2c+1) = 6c+3

28(3c) - 9 = 84c-9

we move the 6c+3 to the other side of the equation by subtracting 6c+3 from both sides

84c-9 - 6c - 3 = 0

78c - 12 = 0

isolate the variable by adding 12 to both sides

78c = 12

then divide both sides by 78

c = 12/78

simplify

c = 12/78 = 2/13

**c = 2/13**

I hope this explanation helped you :)

YourAverageDummy Jan 27, 2023